Stories for children - Wilde, Oscar 1854-1900.; Lynch, Patrick James (New York Macmillan Maxwell Macmillan International Pub. Group, 1991)
Presents Wilde's well-known Selfish Giant, Nightingale and the Rose, Devoted Friend, Happy Prince, Remarkable Rocket, and Young King.
"First published in 1990 by Simon & Schuster Young Books, London, England"--T.p. verso.
Keywords: Fairy tales -- Ireland; Children's stories, English; Fairy tales; Short stories